Exploring the role of teaching assistants in an early literacy intervention programme - Johnson, Gillian (2015)
This study reports research into the role and deployment of teaching assistants who were implementing a literacy intervention - the Fischer Family Trust Wave 3 (FFTW3). A conceptual framework was devised to inform and support the creation, progression and interpretation of the research, drawing upon a postmodern perspective and principles associated with pragmatism and phronesis or practical wisdom. A multiple-case study approach was adopted, using interviews and observations, focusing on six teaching assistants across two local authorities, with the aim of exploring the teaching assistants' implementation of the FFTW3 programme. Analysis was informed by a grounded theory approach where a constant comparison of data was used to create themes. The findings are presented as case reports for each teaching assistant, followed by a cross-case analysis. Findings revealed that the FFTW3 programme provided unique opportunities for sustainable intervention practices which, it is argued, have implications beyond the boundaries of this research. Furthermore, there was considerable evidence that despite supportive structures for the implementation of the programme, barriers to effective deployment persisted in most contexts. The findings raise questions in relation to policy agendas which have not sufficiently clarified the ways in which teaching assistants should be deployed or supported. The implications from this study have relevance for both school systems and educational policy.